Antimicrobial Susceptibility and Detection of Virulence-Associated Genes in Escherichia coli Strains Isolated from Commercial Broilers - Tímea Kocúreková; Lívia Karahutová; Dobroslava Bujňáková (MDPI AG, 2021)
The aim of this study was to investigate the presence of iron-uptake and virulence genes, antibiotic resistance profiles, and phylogenetic relatedness in 115 Escherichia coli (E. coli) strains isolated from broilers in Slovakia and to determine their potential threat to human health. The most frequent phylogroups were B1 (37%) and A (21%), and 33.9% strains were included in pathogenic groups. The commonly observed iron-uptake genes were feoB (94%), sitA (83%), and iutA (58%). Protectins (iss, kpsMTII) were identified in 30% of samples. Four percent of B2-associated broilers carried the papC (P fimbria) gene connected with upper urinary tract infection. The dominant resistance was to tetracycline (49%), ampicillin (66%), ampicillin + sulbactam (27%), ciprofloxacin (61%), and trimethoprim + sulfonamide (34%); moreover, sporadically occurring resistance to cephalosporins, aminoglycosides, fluoroquinolones, and polypeptide colistin was observed. Genotypic analysis of resistance revealed the presence of blaCTX-M-1 and blaCTX-M-2 in two isolates from broilers. Commercial broilers can be reservoirs of virulent and resistant genes as well as E. coli causing (extra-)intestinal infections, which can be a potential threat to humans via direct contact and food.